2023
DOI: 10.3390/ijerph20064732
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Equitable Access to Rare Disease Diagnosis and Treatment around the World: A Review of Evidence, Policies, and Challenges

Abstract: This document provides a comprehensive summary of evidence on the current situation of rare diseases (RDs) globally and regionally, including conditions, practices, policies, and regulations, as well as the challenges and barriers faced by RD patients, their families, and caregivers. The document builds on a review of academic literature and policies and a process of validation and feedback by a group of seven experts from across the globe. Panelists were selected based on their academic merit, expertise, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 105 publications
0
10
0
Order By: Relevance
“…Knowledge on rare diseases in general population as well as among medical profession is low, for example, a study in India reports that half of the respondents did not know what are the rare diseases 23. Further, Adachi and colleagues reported that healthcare providers, decision makers and the population at large have limited knowledge and awareness of rare diseases and also few opportunities are available to raise awareness and educate key stakeholders 24. In addition, the research team noted that there was insufficient number of specialised staff in Zanzibar.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge on rare diseases in general population as well as among medical profession is low, for example, a study in India reports that half of the respondents did not know what are the rare diseases 23. Further, Adachi and colleagues reported that healthcare providers, decision makers and the population at large have limited knowledge and awareness of rare diseases and also few opportunities are available to raise awareness and educate key stakeholders 24. In addition, the research team noted that there was insufficient number of specialised staff in Zanzibar.…”
Section: Discussionmentioning
confidence: 99%
“…As happened with our patient, because of lack of economic resources the genetic exams were not performed early; therefore, the patient was misdiagnosed for over 8 years. In a different study, it is mentioned that many countries, including countries in Latin America, lack or have limited evidence of the economic impact of rare diseases [ 24 ]. Moreover, a misdiagnosis is associated with mental health problems, caregiving burdens, deteriorated health and quality of life [ 24 ], and the process of seeking a diagnosis has been reported as mentally and emotionally draining for patients and their families [ [25] , [26] ].…”
Section: Discussionmentioning
confidence: 99%
“…Underrepresentation of minority groups may be related to the globally recognized barriers to access to RD diagnosis, specialized care and social support [ 72 , 73 ], and other determinants of lack of participation in research [ 74 , 75 ]. Spurred by these findings, the RDCRN has established a cross-consortia Diversity Committee to identify actions to support and expand the participation and engagement of research participants, family members, advocates, and research staff from underrepresented or marginalized communities.…”
Section: Discussionmentioning
confidence: 99%